2013
DOI: 10.1155/2013/527078
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Lighting and Noise Levels and Productivity of the Occupants in Automotive Assembly Industry

Abstract: Work environment affects human productivity and his performance. The aims of this study were to investigate the effects of lighting and noise levels on human productivity in the automotive assembly industry. Method. Subjects were 181 workers from different parts of an automobile assembly industry. Illuminance (Lx) at the height of 30 inches from the surface of work station and noise (dBA) were locally measured. Also human productivity by the Goldsmith and Hersey scale (1980) was measured. Data were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
2
24
1
1
Order By: Relevance
“…These indirect effects corroborate the important role of perceptions of developmental support from co-workers and supervisory mentors for the promotion of work engagement (Spell, Eby, and Vandenberg 2014). In contrast to previous findings (Parsons 2000;Bakker and Demerouti 2007;Fuß et al 2008;Avey, Luthans, and Jensen 2009;Kjellstrom, Holmer, and Lemke 2009;Demerouti and Bakker 2011;Akbari et al 2013;Xiang et al 2014;Bambra et al 2014;Rourke 2014;Albrecht et al 2015;de Neve, Krekel, and Ward 2018), we did not observe direct impacts from physical working conditions, social support provided by supervisors and colleagues, or work-family conflict on either well-being or work outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These indirect effects corroborate the important role of perceptions of developmental support from co-workers and supervisory mentors for the promotion of work engagement (Spell, Eby, and Vandenberg 2014). In contrast to previous findings (Parsons 2000;Bakker and Demerouti 2007;Fuß et al 2008;Avey, Luthans, and Jensen 2009;Kjellstrom, Holmer, and Lemke 2009;Demerouti and Bakker 2011;Akbari et al 2013;Xiang et al 2014;Bambra et al 2014;Rourke 2014;Albrecht et al 2015;de Neve, Krekel, and Ward 2018), we did not observe direct impacts from physical working conditions, social support provided by supervisors and colleagues, or work-family conflict on either well-being or work outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Work in apparel factories typically demands prolonged fixed posture, repetitive movements, and physical hazards, such as improper lighting, heat and cold stress, humidity, poor air quality and circulation, and noise. These factors may significantly influence health, productivity and performance (Parsons 2000;Kjellstrom, Holmer, and Lemke 2009;Akbari et al 2013;Xiang et al 2014), however there is also somethough considerably limitedevidence that they may not be influential for happiness (Loscocco and Spitze 1990) and job satisfaction (Klitzman and Stellman 1989).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The measurements were done on December 21, coinciding with the first day of January between 8 to 10 and 14 to 16 because in the early hours and the end of the day, natural light intensity on the surface of the horizontal and vertical level is at its minimum (27). To compare the amount of measured lighting intensity (natural and artificial lighting) with the standard levels, the technical committee policies based on the occupational safety and health, and Iranian occupational safety and health announced 2016 were used, which were according to the standards of lighting engineering association of North America (30). To calculate the number of lamps in the lumen illumination method, the room index was needed (Kr); coefficients of reflection (coefficient of reflectance floor [ρfc], coefficient of reflectance ceiling [ρcc], coefficient of reflectance walls [ρw]); the maximum allowed distance between the lamps (MH), depending on installation height from floor lamps or ceiling to floor height and distribution curve of the lamp and sort reflector; coefficient of utilization, maintenance factor; and unit area and luminous flux of each lamp (IES tables).…”
Section: Methodsmentioning
confidence: 99%
“…High-pressure mercury lamps were used to redesign. This group of lamps is extensively applied in large places, which do not need high coloring, such as warehouses, industrial production halls, and stadiums with a 6 to 12 meter height (30). Since the installation of high-pressure mercury lamps were focused on several lines, 84 lamps should be put in four 21-one lines.…”
Section: Unit No 25mentioning
confidence: 99%
“…Light intensity has always been important for human existence since it greatly influences sleep, alertness, melatonin and cortisol levels, blood pressure, pulse, respiration rates, brain activity and biorhythm (Wurtman, 1975). It is suggested that lighting enhances the overall performance in the workplace (assembly) as well as learning environments (Akbari, Dehghan, Azmoon, & Forouharmajd, 2013). Classroom lightning has been found to be related to student learning in various ways (Winterbottom & Wilkins, 2009).…”
Section: Light Intensitymentioning
confidence: 99%